Entertaining the Nation : American Drama in the Eighteenth and Nineteenth Centuries - Miller, Tice L. (Book collections on Project MUSE., 2007)
In this survey of eighteenth- and nineteenth-century American drama, Tice L. Miller examines American plays written before a canon was established in American dramatic literature and provides analyses central to the culture that produced them. Entertaining the Nation: American Drama in the Eighteenth and Nineteenth Centuries evaluates plays in the early years of the republic, reveals shifts in taste from the classical to the contemporary in the 1840s and 1850s, and considers the increasing influence of realism at the end of the nineteenth century. Miller explores the r.